Root biomass, root:shoot ratio and belowground carbon stocks in the open savannahs of Roraima, Brazilian Amazonia - Barbosa, Reinaldo Imbrozio; Silva dos Santos, Jhonson Reginaldo; Mariana, Souza da Cunha; Pimentel, Tânia Pena; Fearnside, Philip Martin (Australian Journal of Botany, 2012)
Biomass of roots, the root:shoot ratio (ratio of below-to aboveground biomass) and carbon stocks belowground (to 100-cm depth) were estimated in different open savannah environments in the extreme north of the Brazilian Amazon. Sampling was conducted in permanent plots established in two open savannah areas in the state of Roraima. We identified four phytopedounits in the 27 plots sampled in two areas: four in dry grasslands on Argisol/Ultisol soils (DG-Arg), eight in dry grasslands on Latosol/Oxisol soils (DG-Lts), five in a mosaic of grasslands with savannah-parkland on Latosol/Oxisol soils (GP-Lts) and 10 in seasonally flooded (wet) grasslands on Hydromorphic/Entisol soils (WG-Hyd). Fine roots (>2mm diameter) dominated the 0100-cm vertical profile in the four phytopedounits (>92.5%). Biomass of the roots in WG-Hyd (29.52±7.15Mgha-1) was significantly higher as compared with the other phytopedounits studied, although the carbon stocks did not differ among the phytopedounits (6.207.21MgCha -1). The largest concentration of roots was found in the upper three 10-cm sections of the soil profile, ranging from 56.3 to 82.9% in the four environments. The root:shoot ratio based only on living biomass of roots with diameter <2mm (standard Intergovernmental Panel on Climate Change methodology) ranged from 0 for seasonally flooded grasslands to 0.070.20 for unflooded grasslands on clay soils. The results indicate that the root:shoot ratio (expansion factor) for belowground biomass in open savannah ecosystems in the northern Amazon are low and differ from the default values used in Brazil's reference report to the Climate Convention. © 2012 CSIRO.
Keywords: Aboveground Biomass; Arid Region; Belowground Biomass; Carbon Sequestration; Clay Soil; Entisol; Flooded Soil; Intergovernmental Panel On Climate Change; Oxisol; Root/shoot Ratio; Sampling; Savanna; Seasonality; Soil Profile; Ultisol; Roraima